Building Digital Trust in Jakarta’s Micro and Small Enterprises: From Awareness to Adaptation - Marcel, Marcel; Monica, Katherin (Universitas Bina Darma, 2025)
Digital transformation opens many opportunities for micro, small, and medium enterprises (MSMEs) while also creating new challenges in security and trust. This study examines how MSMEs in Jakarta build digital trust through basic information security practices using a mixed-method approach. A survey involving 30 MSMEs showed that 70 percent of respondents understood the importance of strong passwords and 80 percent were aware of phishing risks. However, only 40 percent used two-factor authentication and 20 percent followed formal security guidelines. Interviews with ten business owners revealed that awareness often develops after personal experiences with fraud, while adaptive strategies such as self-learning, small internal training sessions, and the use of built-in security tools help them cope with limited knowledge and resources. The integration of quantitative and qualitative findings resulted in a conceptual model of incremental digital trust adaptation that progresses through awareness, practical adaptation, and gradual governance. Theoretically, the model explains digital trust as a continuous and context-based process within MSMEs. Practically, it provides guidance for governments, business associations, and digital platforms in creating simple, scalable, and realistic programs to strengthen the digital resilience of small enterprises.